2006
DOI: 10.1007/s10620-006-9080-x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Features of Chronic Nonspecific Multiple Ulcers of the Small Intestine: Comparison with Nonsteroidal Anti-inflammatory Drug-Induced Enteropathy

Abstract: Chronic nonspecific multiple ulcers of the small intestine (CNSU) and nonsteroidal anti-inflammatory drug-induced enteropathy (NSAID-enteropathy) share common clinicopathologic features characterized by histologically nonspecific ulcers and persistent blood loss. The aim was to compare enteroscopic findings between CNSU and NSAID-enteropathy. Four patients with CNSU and five patients with NSAID-enteropathy were examined by enteroscopies. The site of involvement was heterogeneous in NSAID-enteropathy, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 26 publications
4
39
0
Order By: Relevance
“…The sensitivity allowed for the detection of small intestinal lesions, such as red spots, erosions, ulcers, and ulcer scars (1). In addition, another observational study suggested that small intestinal ulcers in NSAID-induced enteropathy occurred in multiplicity either simultaneously or metachronously and improved rapidly after drug discontinuation (15). In the present case, capsule endoscopy showed mild stenosis with multiple ulcerative scars in the small intestine, in addition to erosion.…”
Section: Discussionsupporting
confidence: 51%
“…The sensitivity allowed for the detection of small intestinal lesions, such as red spots, erosions, ulcers, and ulcer scars (1). In addition, another observational study suggested that small intestinal ulcers in NSAID-induced enteropathy occurred in multiplicity either simultaneously or metachronously and improved rapidly after drug discontinuation (15). In the present case, capsule endoscopy showed mild stenosis with multiple ulcerative scars in the small intestine, in addition to erosion.…”
Section: Discussionsupporting
confidence: 51%
“…In differential diagnosis of CMUSE, first of all Crohn's disease (9,15), NSAIDs-induced enteropathy (9,35), tuberculosis and other infections of the small bowel (8,9,20), Behcet disease (19,21,24) and malignancies must be excluded. It is a well-known fact, that the majority of extranodal malignant lymphoma involves the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported on an unusual form of enteropathy of unknown etiology, referred to as chronic nonspecific multiple ulcers of the small intestine (CNSU), which is characterized by chronic blood and protein loss through persistent small intestinal ulcers [4][5][6]. Although this rare but distinct clinicopathologic condition was initially reported in the Japanese literature by Okabe and Sakimura [7], the term ''nonspecific'' in its nomenclature which refers to the nonspecific histology of the ulcers has occasionally led to the misinterpretation of the disease as any condition with small intestinal ulcers of undetermined etiology.…”
Section: Introductionmentioning
confidence: 99%